(untitled) (Andamios, Revista de Investigación Social, 2008)
The author proposes a reading of Marxism that rescues the creative potential of the materialist conception of history, tied to the emancipatory dimension of Marxist socialism. The recovery of this notion implies distancing Marxism from historic productivist/progressive philosophies without failing to recognize its debt to positivism, but highlighting a richer and more multidimensional vision of history.